Aprendi no insta! : os studygrams e a educação online de biologia - COELHO, Yuri Cavaleiro de Macêdo (Universidade Federal do Pará, 2023)
Studygrams are profiles on the social network Instagram that share different types of digital content with an educational, informative and instructional bias, such as study routines and materials. The growth of this type of profile highlights the need for contemporary society to learn, teach and obtain information in ways different from traditional ones. Faced with this new movement in the use of social networks on the internet in education, this study aimed to understand the difficulties and possibilities of using Studygrams in the context of teaching Biology learning and training for citizenship, in online education initiatives in higher education. . The research is characterized as qualitative, within the approaches of netnographic research and research-education in cyberculture. The information was recorded in a hypertextual field notebook and submitted to Discursive Textual Analysis. In the netnographic research, we explored ten Studygrams with high engagement that published content related to Biology. The context of research-training in cyberculture was based on an Interactive Didactic Design (IDD) for the creation and management of 17 Studygrams, implemented in a private Higher Education Institution in Belém, capital of the state of Pará, with 154 students from the area of health – Nutrition, Physiotherapy and Pharmacy – who were studying Histology and Embryology. The results reveal that Studygrams represent a new culture of learning and teaching, which can be used in online Biology education as a source of information and a space for carrying out activities. The IDD activities allowed students to approach histological knowledge in an informative, explanatory, critical, interdisciplinary and contextualized way; to elaborate and share (co)authorships and academic experiences; and horizontalize the relationship with the teacher. On the other hand, students reported difficulties in selecting, organizing and presenting in a succinct, logical and creative way the large amount of information available on the internet on the topics covered. Although they emphasize that real-time monitoring of the dynamics and actions of the teams and their Studygrams demands time, planning, organization and increases the workload outside the classroom, the professors-researchers point out that working in online Biology education potentiated co-participation in (co)authorship shared virtually; the exercise of creative capacity of pedagogical intentions for hypertextual, interactive and plural environments; the appropriation of the continuous training path; and the resignification of teaching and training experiences. The experiences with the IDD raised elements with the potential to guide processes of evaluation of the learning of biological contents and the development of values and attitudes towards citizenship, as well as to support the construction of evaluation instruments capable of bringing data on the real impact of the IDD and providing opportunities reflections on students' understanding and performance; the obstacles that prevent them from achieving better performances and developments; and the different skills that can be promoted in online Biology education in higher education.